Dead-Time Analysis and Optimization for LLC Resonant Converter Using IGBT - Xiaoyong ZHANG; Qing ZHANG; Peinan RAO; Huibo SUN; Jia ZHAO (机车电传动)
In ZVS-LLC resonant converter, proper dead time is essential for IGBT to realize zero-voltage-switching. In fact,the output capacitor of the IGBT is not constant when the IGBT is switching off, which makes the design of the dead-time relatively complicated. The switching characteristics of the IGBT was analyzed, indicating that in the LLC resonant circuit, the higher the working temperature and the heavier the load power were, the less conducive to realize the soft-switching of the IGBT. It was proposed that the minimum and maximum dead-time should be designed at the full load and the maximum working temperature condition. Finally, a 60 kW LLC converter was built to verify the correctness of the optimal design. The experiment results basically consistent with the theoretical calculation results.